6-Gingerol abates benzo[a]pyrene-induced colonic injury via suppression of oxido-inflammatory stress responses in BALB/c mice (2019)
Exposure to benzo[a]pyrene (BaP), the most toxic polycyclic aromatic hydrocarbon and a procarcinogen, is a global health concern which necessitates preventive measures. [6]-Gingerol (6-G), the most pharmacologically active constituent of ginger has been reported to promote gut health in various experimental settings. This study investigated the role of 6-G in BaP-induced colonic oxidative and inflammatory stress responses in mice. Experimental mice were randomly assigned into five groups of eight mice each and were orally gavage with BaP (125 mg/kg) singly or in combination with 6-G at 50 and 100 mg/kg for 14 consecutive days. Following sacrifice, the colonic activities of superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), myeloperoxidase (MPO) as well as levels of glutathione (GSH), nitrites and lipid peroxidation (LPO) were assessed spectrophotometrically. Moreover, colonic concentration of epoxide hydrolase (EPXH), tumor necrosis factor alpha (TNF-α), interleukin-1 β (IL-1β), cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) were assessed using ELISA. Administration of 6-G augmented BaP detoxification and colonic antioxidant status by increasing the EPXH, GST, SOD and CAT activities, GSH level with concomitant decrease in MDA level when compared with BaP alone group. In addition, 6-G suppressed BaP-induced colonic inflammation by decreasing MPO activity as well as nitrites, TNF-α, IL-1β, COX-2 and iNOS levels when compared with BaP alone group. In conclusion, 6-G protected against a decrease in colonic epoxide detoxifying enzymes and antioxidant defense mechanisms caused by BaP.